THE “GALLIC MORBIDITY” (SYPHILIS) DURING THE LATE COLONIAL PERIOD: THE TENSION BETWEEN THE LEGAL-RELIGIOUS MORAL AND HYGIENIST RATIONALITY. THE CASE OF THE PETRONA SLAVE. SANTIAGO, CHILE 1806-1808. - Celis Valderrama, Nicolás (Revista de Historia Social y de las Mentalidades, 2014)
The present article aims to show the tension between the legal-religious moral and the rational hygienist paradigm shown through the legal case followed by Mr. Nicolás Ambrosi Churale with Mr. Francisco Ramón Vicuña, about: ‘nullity of the sale of a sick slave from Gallic. Sale of the Petrona slave, since August 29th, 1806, until August 26th, 1808”. To accomplish this, we will use the encounter of two paradigms, one assumed by the litigants and their representatives (legal-religious moral), and the other one assumed by doctors and surgeons (hygienist rational) summoned during trial. This article does not intend to lose track of the traces kept by the file itself, being this the column of this text, and assuming that the intended approach to use is oriented towards the impact of the disease, beyond the litigation of the sale nullity.